SYSTEM FOR SELECTING EXTRACULAR TALENTS USING SIMPLE ADDITIVE WEIGHTING METHOD (SAW) AT MADRASAH IBTIDAIYAH (MI) ISMARIA AL-QUR'ANIYYAH BANDARLAMPUNG - Seli Puri Andani; Sri Lestari (Proceeding International Conference on Information Technology and Business, 2020)
Madrasah Ibtidaiyah (MI) Ismaria Al-Qur'aniyyah had 10 extracurricular activities, e.g., Futsal Men, Women's Futsal, Creative Dance, Scouting, Men's Basketball, Women's Basketball, Tekwondo, Soccer, Choir, and Regional Dance. The problem statement of this research was that there was a difficulty to determine the students’ interest to choose the extracurricular activity. Therefore, there was a need for a system to improve the good education quality, especially in choosing the extracurricular activity based on the 3rd grade students’ interests. The method used in this study was the Method Simple Additive Weighting (SAW).Keywords: Recommendation System, Extracurricular, SAW